Translation in Enlightenment Spain - García Garrosa, María Jesús (The Routledge companion to the Hispanic Enlightenment, 2019)
This chapter treats translation as an intellectual activity which promoted the circulation of texts and ideas, encouraging enrichment and advance in all fields of knowledge in eighteenth-century Spain. It begins with an analysis of the debate in Spanish society between those who supported translation because of its contribution to cultural interplay and opening Spain to renewal, and those who opposed the changes which they believed it might bring to the nation’s culture. This leads to a description and analysis of the main fields in which translation was most evident (literature, the sciences, thought and education).